Pengembangan Urban Farming di Kota Surabaya dengan Inovasi Bisnis : Model BMC (Business Model Canvas): Development of Urban Farming in the City of Surabaya with Business Innovation: BMC Model (Business Model Canvas) - Yuliati, Nuriah; Nurhadi, Eko; Atasa, Dita; Baik, Stevi Putri Afdolvina (Jurnal Ilmiah Manajemen Agribisnis, 2024)
Urban farmers create creative ways in the form of entrepreneurial innovation to develop urban farming. Women Farming Groups (KWT) and Farmer Groups (Poktan) can become profitable businesses because of higher quality human resources and production quality orientation. The research objective is to analyze urban farming business innovation in the city of Surabaya using the BMC (Business Model Canvas) model. The research was carried out on 5 Women Farmer Groups (KWT) and Farmer Groups (Poktan) in the City of Surabaya, namely, Guyub Rukun Farmer Women Group, Yurga Farm Farmer Group, Serpis Farmer Group, Sri Rejeki Jitu Farmer Group, and Dorang Cinta Farmer Woman Group. The analysis used is qualitative analysis by describing the stages of innovation with business models on the 9 Business Model Canvas (BMC). Research using qualitative methods was used in 5 KWTs and Poktans. Therefore, key informants were selected from each chairman of the KWT and Poktan. The results of the research were that KWT Guyub Rukun received the lowest revenue and Poktan Serpis received the highest revenue. This is because the revenue flow only comes from the sale of harvested crops and only has one main partner. The development of an urban farming business using the BMC (Business Model Canvas) model can be used by business people as a basis for developing strategies and taking steps to develop better so that with BMC they can discover the advantages and disadvantages of each KWT and Poktan.